Evaluation of Polymeric Matrix Loaded with Melatonin for Wound Dressing - Beata Kaczmarek-Szczepańska; Justyna Ostrowska; Justyna Kozłowska; Zofia Szota; Anna A. Brożyna; Rita Dreier; Russel J. Reiter; Andrzej T. Slominski; Kerstin Steinbrink; Konrad Kleszczyński (International Journal of Molecular Sciences, 2021)
The development of scaffolds mimicking the extracellular matrix containing bioactive substances has great potential in tissue engineering and wound healing applications. This study investigates melatonin—a methoxyindole present in almost all biological systems. Melatonin is a bioregulator in terms of its potential clinical importance for future therapies of cutaneous diseases. Mammalian skin is not only a prominent melatonin target, but also produces and rapidly metabolizes the multifunctional methoxyindole to biologically active metabolites. In our methodology, chitosan/collagen (CTS/Coll)-contained biomaterials are blended with melatonin at different doses to fabricate biomimetic hybrid scaffolds. We use rat tail tendon- and Salmo salar fish skin-derived collagens to assess biophysical and cellular properties by (i) Fourier transform infrared spectroscopy—attenuated total reflectance (FTIR–ATR), (ii) thermogravimetric analysis (TG), (iii) scanning electron microscope (SEM), and (iv) proliferation ratio of cutaneous cells in vitro. Our results indicate that melatonin itself does not negatively affect biophysical properties of melatonin-immobilized hybrid scaffolds, but it induces a pronounced elevation of cell viability within human epidermal keratinocytes (NHEK), dermal fibroblasts (NHDF), and reference melanoma cells. These results demonstrate that this indoleamine accelerates re-epithelialization. This delivery is a promising technique for additional explorations in future dermatotherapy and protective skin medicine.